Analisis Komparatif Eklesiologi Tata Gereja 2010 Dan 2021 Gereja Kristen Pemancar Injil - Julianus Mojau (BIA': Jurnal Teologi dan Pendidikan Kristen Kontekstual, 2022)
Abstract: This article is the result of research on the comparison of the ecclesiology of the 2010 and 2021 Church Order of the Evangelist Christian Church (Gereja Kristen Pemancar Injil/GKPI). By using qualitative research methods through library research, the researcher does a comparative analysis of the ecclesiological reasons the GKPI pioneer separated from the Indonesian Christian Gospel Tabernacle Church (Kemah Injil Gereja Masehi Indonesia/KINGMI) in 1959 and the differences between the ecclesiology of the 2010 and the 2021 GKPI Church Orders. The results of the study show the following. First, the ecclesiological reason for the GKPI pioneer separating from KINGMI was to develop an ecclesiology beyond KINGMIâ€™s docetic tendencies and develop a holistic-empirical ecclesiology that answers the life challenges of congregation members and the peoples of North and East Kalimantan. Second, the 2010 GKPI church order ecclesiology, which has a â€œpresbyterial-synodalâ€ pattern with bureaucratic and feudal characteristics, tends to weaken the autonomy of the congregations in the GKPI Synod. Third, the 2021 Church Order ecclesiology develops a synodal-presbyterial institutional pattern that prioritizes equal and democratic relations between congregations and between congregations and synod. Fourth, both the ecclesiology of the 2010 Church Order and the 2021 Church Order do not sufficiently consider the culture of the Dayak people. Fifth, both the 2010 and 2021 Church Order pay enough attention to the Churchâ€™s social work in the midst of the North and East Kalimantanâ€™s society.Â  However, this still needs to integrate church order, liturgy, understanding of faith and the main tasks of the churchâ€™s social work so that the presence of the GKPI can become the ritual body of Christ as well as the social body of Christ. Â Keywords: ecclesiology, Church Order, GKPI, contextual. Â Abstrak: Artikel ini adalah hasil penelitian tentang perbandingan eklesiologi Tata Gereja 2010 dan 2021 Gereja Kristen Pemancar Injil (GKPI). Dengan menggunakan metode penelitian kualitatif melalui jenis penelitian kepustakaan peneliti melakukan analisis komparatif tentang alasan eklesiologis perintis GKPI memisahkan diri dari Kemah Injil Gereja Masehi Indonesia (KINGMI) tahun 1959 dan perbedaan eklesiologi Tata Gereja 2010 dan 2021 GKPI.Â  Hasil penelitian ini memperlihatkan hal-hal sebagai berikut. Pertama, alasan eklesiologis perintis GKPI memsahkan diri KINGMI tahun 1959 adalah panggilan Injili untuk melampaui kecenderungan eklesiologi dokestis KINGMI dan mengembangkan suatu eklesiologi holistik-empirik yang menjawab tantangan kehidupan sehari-hari warga jemaat dan masyarakat Kalimantan Utara dan Timur pada saat itu. Kedua, eklesiologi Tata Gereja 2010 yang berpola kelembagaan sinodal-presbiterial berciri birokratis dan feudal cenderung melemahkan kemandirian jemaat-jemaat dalam Sinode GKPI. Ketiga, eklesiologi Tata Gereja 2021 yang mengembangkan pola kelembagaan presbyterial-sinodal yang mengedepankan hubungan setara dan demokrats antarjemaat dan antara jemaat dan sinode.Â  Keempat, baik eklesiologi Tata Gereja 2010 maupun Tata Gereja 2021 Â tidak cukup mempertimbangkan budaya orang Dayak. Kelima, baik Tata Gereja 2010 maupun 2021 cukup memberi perhatian pada tugas/karyaÂ  sosial Gereja di tengah-tengah masyarakat. Namun perhatian ini masih perlu mengintegrasikan tata gereja, liturgi, pemahaman iman dan pokok-pokok tugas/karya sosial gereja sehingga dapat menjadikan kehadiran GKPI menjadi Gereja publik yang meragakan tubuh ritual Kristus sekaligus tubuh sosial Kristus. Â Kata-kata Kunci: eklesiologi, Tata Gereja, GKPI, Kontekstual.Â  Â  Â Â